2020
DOI: 10.1177/0272989x20904357
|View full text |Cite
|
Sign up to set email alerts
|

When Does the Incremental Risk Format Aid Informed Medical Decisions? The Role of Learning, Feedback, and Number of Treatment Options

Abstract: Background. Informed medical decisions require understanding the benefits and risks of treatments. This entails comparing treatment outcomes to a control group. The incremental risk format has been recommended as it directly visualizes the differences between treatment and control group in 1 graph, whereas they have to be calculated from 2 separate graphs in the total risk format. We investigated when the incremental risk format aids understanding. Methods. In 2 experiments, participants received information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Some studies have found that visualizations are valued by carriers of BRCA1/2 pathogenic variants[ 36 , 37 ] and result in higher decision satisfaction[ 38 ], but have found no clear differences in comprehension, well-being or treatment intentions[ 38 , 39 ]. Studies communicating breast cancer risk with ‘incremental’ icon arrays containing three or more colors found that these have not fared as well as other formats[ 36 , 37 , 40 ], in line with research finding that this kind of icon array can be difficult to interpret without training[ 41 ]. BRCA risk communication studies using simpler icon arrays have been inconclusive[ 39 , 42 ] or have reported benefits[ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 75%
“…Some studies have found that visualizations are valued by carriers of BRCA1/2 pathogenic variants[ 36 , 37 ] and result in higher decision satisfaction[ 38 ], but have found no clear differences in comprehension, well-being or treatment intentions[ 38 , 39 ]. Studies communicating breast cancer risk with ‘incremental’ icon arrays containing three or more colors found that these have not fared as well as other formats[ 36 , 37 , 40 ], in line with research finding that this kind of icon array can be difficult to interpret without training[ 41 ]. BRCA risk communication studies using simpler icon arrays have been inconclusive[ 39 , 42 ] or have reported benefits[ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 75%
“…Where possible in decision aids, effect sizes should be presented as either independent event rates (using simple frequencies or percentage formats) and/or as an incremental (or absolute) risk increase or decrease from a baseline risk frequency. 3,6,7 A hypothetical example would be that 5 out of 100 (5%) people in a particular population group are likely to die from disease X over the next year without receiving treatment A. This could be described as the baseline frequency or control event rate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been consistently recommended that relative risk presentations alone should be avoided as they tend to magnify risk perceptions and decrease understanding in both patients and clinicians. [7][8][9][10][11][12][13] Similarly, the number needed to treat and number needed to harm formats should also be avoided in patient decision aids, as they lead to overestimates of treatment effects and are poorly understood. 14 There is no advantage to providing baseline risk alongside relative risks, and this practice should continue to be avoided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is commonly agreed that informed medical decisions require profound understanding of specific benefits and risks of treatments, conclusive information for a specific situation is often lacking. 1 As an example, this was the case in about half of the 3000 treatment options compiled in the BMJ Clinical Evidence compendium 2013 with another seven percent requiring (individualized) trade-offs between benefits and harms. 2 Thus, when prescribing drugs, clinicians constantly need to make treatment decisions for patients without knowing the best choice of often multiple available options.…”
Section: Introductionmentioning
confidence: 99%